Preliminary findings from the youth entrepreneurs: students entrepreneurs' characteristics and motivation / Yasmin Kamall Khan ... [et al.] - Khan, Yasmin Kamall; Abd Halil, Nurul Hafez; Syed Marzuki, Sharifah Zannierah (2018)
Entrepreneurship contributes to the economic growth of a nation. However, the number of individuals engaged in entrepreneurial remains low, instead of the high unemployment rate. This inconsistency between youth attitudes and acts highlights the need for programs that foster the development of entrepreneurship in today's youths. Before an appropriate program can be designed for these youths, we have to understand their character and motivation. Data for this study was collected using qualitative method. The qualitative data come from semi-structured interviews. This initial interview was conducted by inviting three young entrepreneurs from the Masters in Applied Entrepreneurship in UiTM. The results show that youth's characteristics are influenced by self-efficacy, initiative and information seeking, while their motivation is driven by passion and family support are important for promoting entrepreneurial intent among young adults. Youths, have a creative way of thinking and is motivated to run their businesses with an appropriate exposure in the higher learning institution.